Introduction. Critical Issues Emerging from the Study of Unspent Funds - Deval Desai; Sruthi Herbert; Christine Lutringer (Revue Internationale de Politique de Développement)
This chapter introduces the thematic volume The Puzzle of Unspent Funds. It explains the scope of the Volume, which conducts a cross-context analysis of unspent funds in its other individual chapters. These chapters span two different socio-economic and institutional contexts: India and Italy, thus presenting valuable points of comparison. They map underspending through the four fiscal phases of collection, allocation, use and monitoring of funds, analysing these phases through the key notions of fiscal architecture and administrative structures, which this chapter explains before emphasizing the main contributions of each individual chapter. This Volume provides an innovative perspective to analyse institutional design and reforms in multilevel governance contexts; administrative and bureaucratic state practices; modalities of state-society engagement; and mechanisms to increase democratic accountability.